Get started with Minecraft - Moltz, John (Peachpit Press, 2014)
"Minecraft comes with no real instructions, so surviving your first days in Minecraft can be full of frustrations, once you get the game installed. Don't worry. In this downloadable video, we'll explain how to get and install the game and survive your first day. You'll also see how to expand the game and play with friends."--Resource description page.
Title from resource description page (viewed February 4, 2015). - Date of publication taken from resource description page
Keywords: Minecraft (Game); Video games; Video Games; Minecraft (Jeu); Jeux vidéo; video games; Electronic videos